Management and Public Management - Feldman, Martha S. (Academy of Management Journal, 2005)
The article discusses effective management in the public sector. As the U.S. government's response to Hurricane Katrina revealed, the cost of poor management can be high. As former Western Digital chief executive Roger Johnson discovered when he took a public position in Washington, DC, government employees are often quite adept in their particular areas of expertise, but often lack management skills. The author believes three things must be done. First, political pressure should be exerted to demand better public management. Second, public managers should have access to more training. And third, more research needs to be done into the management of public organizations.